PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN PENGUNGKAPAN CSR TERHADAP NILAI PERUSAHAAN (Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2016 – 2020) - Sri Kawuri (LPPM STIE Anindyaguna, 2021)
The research is intended to determinate the effect of size, profitability, and disclosure corporate social responsibility on firm value in manufacturing companies which listed on the Indonesia Stock Exchange 2016 - 2020. Independent variables of this research is size, profitability, and disclosure corporate social responsibility. Dependent variable of this research is firm value. The population of this research is manufacturing companies which listed on Indonesia Stock Exchange in the period 2016 – 2020 based on chosen sampling criteria of the population, it draws 41 companies.type of data is secondary data carried by documentary method which conducted by accessin website www.idx.co.id. Result of this research that company size no effect on firm value, profitability positive effect on firm value (ROA), and disclosure corporate social responsibility no effect on firm value Keywords : company size, profitability, and disclosure corporate social responsibility